A STUDY OF LINGUISTIC FEATURES OF REAL ESTATE ADVERTISEMENTS IN ENGLISH VERSUS VIETNAMESE - Ph. D. HỒ THỊ KIỀU OANH (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This thesis mainly aims at setting off linguistic features, their similarities, differences and their frequencies of occurrence in real estate advertising language in English and Vietnamese newspapers, magazines and websites. The data of the study are collected from English, Vietnamese newspapers, magazines and websites specialized in real estate advertising. They are described and contrastively analyzed on semantic and syntactic aspects under qualitative and quantitative approaches to yield more precise points on linguistic features in real estate advertising language. On the basis of a contrastive analysis, the thesis tries to find out some commonly used some linguistic features in real estate advertising language in English and Vietnamese newspapers, magazines and websites. With an eye to partly contributing to better teaching and learning English as a foreign language, specifically to better the awareness of learners in translating and writing an advertisement, some suggested ideas are also included.